Urban tween talk about using mobile phones for learning - Arafeh, Sousan; Kuszpa, M; Weller, M; Mitchell, T (Mobile Learning: Perspectives on Practice and Policy, 2018)
There can be no doubt that mobile technologies are here to stay. Global mobile traffic grew 74 percent in 2015 alone, with 563 million devices and connections added – most of them tablets and Smartphones. This growth has been 4000-fold in the past 10 years and 400 million-fold in the past 15 years (Cisco, 2016). Mobile technologies permeate the lives of 21st century citizens as mainstays of organizational and institutional day-to-day operations, commerce, and communication and as tools used to support individuals' personal, social, and career responsibilities. In both the corporate and educational worlds, e- and m-learning and marketing with mobile technologies are moving forward at breakneck speed with, in many cases, a blurring of traditional sector boundaries. As neither the technology nor the uses are static, exploring practices and policies that underpin this quickly shifting mobile technology context is crucial for ensuring its intelligent, purposeful, and equitable use. This edited book provides a venue for researchers to share their work on mobile learning with a focus on uses for mobiles in informal settings and PK-20 classrooms, language learning, mobile gaming, leadership and policy issues, and what mobile learning in the future may be. It assists researchers and educators to consider and answer questions such as: What is "mobilelearning" today How can mobiles be used to enable learning How is mobile learning crossing or connecting economic, social, and/or cultural sectors How do specific cultural practices with media influence mobile learning (e.g
Keywords: dept.edl